Forms of Understanding for XAI-Explanations - Buschmeier, Hendrik; Buhl, Heike M.; Kern, Friederike; Grimminger, Angela; Beierling, Helen; Fisher, Josephine Beryl; Groß, André; Horwath, Ilona; Klowait, Nils; Lazarov, Stefan Teodorov; Lenke, Michael; Lohmer, Vivien; et al. (Cognitive Systems Research)
Explainability has become an important topic in computer science and artificial intelligence, leading to a subfield called Explainable Artificial Intelligence (XAI). The goal of providing or seeking explanations is to achieve (better) ‘understanding’ on the part of the explainee. However, what it means to ‘understand’ is still not clearly defined, and the concept itself is rarely the subject of scientific investigation. This conceptual article aims to present a model of forms of understanding for XAI-explanations and beyond. From an interdisciplinary perspective bringing together computer science, linguistics, sociology, philosophy and psychology, a definition of understanding and its forms, assessment, and dynamics during the process of giving everyday explanations are explored. Two types of understanding are considered as possible outcomes of explanations, namely enabledness, ‘knowing how’ to do or decide something, and comprehension, ‘knowing that’ – both in different degrees (from shallow to deep). Explanations regularly start with shallow understanding in a specific domain and can lead to deep comprehension and enabledness of the explanandum, which we see as a prerequisite for human users to gain agency. In this process, the increase of comprehension and enabledness are highly interdependent. Against the background of this systematization, special challenges of understanding in XAI are discussed.
Keywords: understanding; explaining; explanations; explainable; AI; interdisciplinarity; comprehension; enabledness; agency

Operando Analysis of the Pre-OER Activation of Metal-Doped Co3O4 Nanoparticle Catalysts - Kampermann, L.; Klein, J.; Wagner, T.; Kotova, A.; Placke-Yan, C.; Yasar, A.; Jacobse, L.; Lasagna, S.; Leppin, Christian; Schulz, S.; Linnemann, Julia; Bergmann, A.; et al. (ACS Catalysis)
Doped Co3O4 nanoparticles are investigated via spectro-electrochemistry in the (pre-) oxygen evolution reaction (OER) regime by tracing the absorption signal of the Co3+ d–d transition under applied bias for getting insight into the catalysts activation and the formation of catalytically active phases. In the low potential regime up to 1.37 VRHE, a rise in the optical absorption signal of the [Co3+]oct d–d transition is observed and attributed to a structural change from [Co2+]tet to [Co3+]oct due to an electrochemically induced surface restructuring with water. For applied potentials higher than 1.37 VRHE an overall offset of the absorption spectra in the UV–vis range, equivalent to a darkening of the materials is detected. This is attributed to the formation of a CoOx(OH)y skin layer as supported by high-energy X-ray diffraction (HE-XRD) measurements. We found that the kinetics of the Co3+ states are heavily influenced by the type of dopant with V-doped Co3O4 exhibiting stable Co3+ states (>20 min) while the Mn-doped Co3O4 Co3+ states reduce within 36 s under reductive bias. We conclude that doping Co3O4 with transition metals affects the formation and potential-dependent thickness of the CoOx(OH)y skin layer as the catalytically active phase and the formation of long-time stable surface Co3+ states after activation in the first OER cycle.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; operando characterization; spectroelectrochemistry

What do metaphors of understanding hide? - Porwol, Philip Fabian; Scharlau, Ingrid (STUDIA NEOFILOLOGICZ: NEROZPRAWY JĘZYKOZNAWCZE (Modern Language Studies: Linguistic Essays))
Many previous studies on the conceptual function of metaphors have focused on their func-tion of highlighting aspects of target concepts. From the beginning of this research, it was knownthat conceptual metaphors also hide aspects of the target concept; however, this as-pect has been less studied. This study builds upon the idea that the hiding aspect of a specific metaphor should be identified in relation to other metaphors for the same concept. A method is presented to detail this relation based on the theory of semantic frames and the FrameNet resource to identify the hidden aspects and apply it to a corpus of 298 elicited metaphor texts on the target concept of understanding. The analysis revealed that certain conceptual aspects are consistently hidden by a majority of metaphors, pointing to patterns in conceptualization. Using this approach, six aspects frequently hidden by metaphors were identified: Sociality, Transfer, Ownership, Perception, Foundation and Duration.

Baked Apples and Bitter Ales: Richard Jefferies, Rural Health, and the Medical Imagination in Amaryllis at the Fair (1887) - Behler, Felix (8th Digital DACH Victorianists Workshop – Mediating Medicine: Health and Illness in the Victorian Age. Organisation: Dr. Julia Ditter (Universität Bremen), Dr. Anne Korfmacher (Universität Graz).)

Negotiating the future: legitimacy and power dynamics in Europe's twin transition - Lenz, Sarah (Sustainable Futures)

In Situ PM‐IRRAS and XPS Analysis of Nitrogen Plasma Surface Modification of Polylactide Thin Films - Golebiowska, Sandra Alicja; Voigt, Markus; de los Arcos, Teresa; Grundmeier, Guido (Surface and Interface Analysis)
ABSTRACT Spin‐coated polylactide (PLA) thin films were exposed to nitrogen plasma for varying time intervals. The progressive etching of the PLA film in direct contact with the nitrogen plasma was monitored in situ using polarization modulated infrared reflection absorption spectroscopy (PM‐IRRAS). No appreciative changes in composition were seen with PM‐IRRAS, indicating that the etching did not significantly affect the bulk composition. Atomic force microscopy characterization of the plasma‐etched films showed that the PLA films are homogeneously etched. Subsequent ex situ XPS analysis of the treated surface revealed the presence of C‐N bonds in the surface‐near region that could be associated with amino and/or amide surface species. PLA films were also alternatively exposed to nitrogen ion beams produced by an electron‐cyclotron‐resonance (ECR) plasma source and were investigated in vacuo by XPS. This treatment revealed the partial substitution of surface oxygen species by nitrogen, resulting in a similar surface modification as in the plasma case. The comparison of XPS data and water contact angle studies suggest that the activated surfaces show a reorientation of macromolecular fragments in the surface‐near region depending on the polarity of the phase with which they are in contact. Under ultra‐high vacuum (UHV) conditions, the surface tends to lower its surface energy, while in contact with the aqueous phase, subsurface polar groups orientate outwards, which enables the formation of hydrogen bonds.

A rate-based model for reactive separation columns with sandwich packings - Franke, Patrick; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y. (Chemical Engineering Science)
Sandwich packings are assembled from two conventional structured packings with different geometrical surface areas stacked alternatingly within a separation column. When operated under partially flooded conditions, they provide significant mass transfer improvement compared to common structured packings. In this work, a rate-based model including novel mass transfer correlations is presented and validated using a comprehensive experimental database for the reactive absorption of CO2 into aqueous monoethanolamine. The proposed rate-based approach is capable of accounting for axial dispersion, thereby enabling the evaluation of the effect of liquid-phase backmixing on the mass transfer performance. The validated rate-based model is used to evaluate the separation performance of sandwich packings. Compared with structured packings, up to 10 % higher mass transfer rates are obtained.
Keywords: Sandwich packings Structured packings Rate-based approach Model validation Ultra-fast X-ray tomography

A contribution to the mechanistic understanding of the improvement of the delamination resistance of adhesives on steel by grit-blasting - Ruhm, Lukas; Neßlinger, Vanessa; Becker, Roman; Meschut, Gerson; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

Interface chemistry and adhesion of thin bilayer Si-organic PECVD barrier films on post-consumer recycled polypropylene - Müller, Hendrik; Cetin, Ali; Dahlmann, Rainer; de los Arcos, Teresa; Grundmeier, Guido (Surface and Coatings Technology)

Spontaneous grafting of nitrobenzenediazonium salt on plasma-modified copper substrates - Su, Jiangling; Muhle, Marius; Nembot, Nelly; Prüßner, Tim; Xie, Xiaofan; Wittstock, Gunther; Grundmeier, Guido (Electrochimica Acta)

Digitale Kompetenzen für Lehrkräfte in der beruflichen Bildung – Beiträge zur Modellierung, Messung und Förderung - Sänger, Niklas
Die digitale Transformation stellt Lehrkräfte vor eine doppelte Herausforderung: Sie sind selbst Lernende im Zuge des Wandels und gleichzeitig dafür verantwortlich, digitale Kompetenzen bei ihren Lernenden zu fördern. Aus Sicht der beruflichen Bildung besteht eine weitere Herausforderung darin, dass Lehrkräfte zwischen zwei inhaltlichen Referenzsystemen – wissenschaftsorientiertem Fachwissen und praxisbezogenem beruflichem Wissen – vermitteln müssen. Bisherige Forschungsarbeiten fokussieren jedoch primär medienpädagogische Aspekte und vernachlässigen den Einfluss der digitalen Transformation auf die fachlichen Lerngegenstände sowie damit verbundene fachdidaktische Implikationen. Die Dissertation adressiert diese Forschungslücke, indem sie untersucht, wie digitale Kompetenzen von Lehrkräften in der beruflichen Bildung konzeptualisiert, empirisch erfasst und curricular integriert werden können. Sie verfolgt dabei drei zentrale Fragestellungen: (1) Wie lassen sich digitale Kompetenzen im Kontext des doppelten Gegenstandsbezugs theoretisch fundieren? (2) Wie kann ein entsprechendes Kompetenzmodell empirisch operationalisiert werden? (3) Welche Implikationen ergeben sich daraus für die curriculare Gestaltung von Lehramtsstudiengängen? Im Rahmen der kumulativen Dissertation wird zunächst das TPACK-Modell kritisch analysiert und für den Kontext der beruflichen Bildung erweitert. Darauf aufbauend wird ein Messinstrument zur Erfassung digitaler Kompetenzen entwickelt und empirisch validiert. Zudem wird ein hochschuldidaktisches Konzept zur curricularen Integration digitaler Kompetenzen entwickelt und reflektiert. Die Ergebnisse zeigen, dass der doppelte Gegenstandsbezug ein zentrales Strukturmerkmal digitaler Kompetenzen in der beruflichen Bildung darstellt und bei der Ausbildung von Lehrkräften systematisch berücksichtigt werden muss. Die Dissertation leistet einen konzeptionellen und empirischen Beitrag für den Diskurs um digitale Kompetenzen in der beruflichen Bildung und gibt konkrete Impulse für die Professionalisierung von Lehrkräften im Zuge der digitalen Transformation.

Didaktische Überlegungen in der Psychologie - Scharlau, Ingrid; Jenert, Tobias (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

Studiengangentwicklung - Jenert, Tobias (Hochschulforschung)
This handbook systematises the current state of knowledge on subjects of higher education research. It examines research, teaching and studies, the transfer of knowledge related to research and teaching as well as universities as organisations and their functions in the education and training systems. By looking at the topics over time, this standard work also provides information on university developments and their current state. The following question is answered in 60 articles: What do we currently know about the topic under discussion, what is the current state of research and what has remained unanswered so far? This book is aimed at higher education, academic and educational research as well as practitioners in higher education development and higher education policy.With contributions byNicole Auferkorte-Michaelis | Julia Backhaus | Ulf Banscherus | Annette Barkhaus | Lukas Baschung | Lorenz Blume | Stefan Böschen | Carla Bohndick | Gesche Brandt | Kolja Briedis | Rainer Bromme | Till Bruckermann | Juri Dachtera | Jennifer Dusdal | Melinda Erdmann | Gregor Fabian | Marian Füssel | Max-Emanuel Geis | Nicolai Götze | Gabriele Gramelsberger | Insa Großkraumbach | Julian Hamann | Christophe Heger | Thomas Heinze | Justus Henke | Sandra Hofhues | Arlette Jappe | Tobias Jenert | Stefan John | Wolfgang Jütte | Marco Kalz | Michael Kerres | Bernd Kleimann | Robert Kordts | Anna Kosmützky | Georg Krücken | Ines Langemeyer | Michelle Latta | Inge Leurs | Avelina Lovis-Schmidt | Sylvi Mauermeister | Marianne Merkt | Björn Möller | Richard Münch | Martin Neugebauer | Axel Oberschelp | Peer Pasternack | Attila Pausits | Axel Philipps | Manuel Pietzonka | Philipp Pohlenz | Justin J. W. Powell | Carole Probst | Martin Reinhart | Gabi Reinmann | Rüdiger Rhein | Heiner Rindermann | Heinke Röbken | Ronny Röwert | Gudrun Rohde | Niclas Schaper | Mandy Schiefner-Rohs | Christian Schneijderberg | Elmar Schüll | Marcel Schütz | Dagmar Simon | Isabel Steinhardt | Jana Stibbe | Friedrich Stratmann | Niels Taubert | Ulrich Teichler | Ewald Terhart | Peter Tremp | Martin Unger | Susanne de Vogel | Klaus Wannemacher | Christian Wassmer | Inka Wertz | Oliver Wieczorek | Johanna Witte | Andrä Wolter | Grit Würmseer

Fostering self-regulated entrepreneurial learning in entrepreneurship education - Fahrbach, Manuel; Jenert, Tobias; Fust, Alexander; Bellwald, Noah; Winkler, Christoph (Annals of Entrepreneurship Education and Pedagogy - 2025)
Keywords: Self-Regulated Learning; Entrepreneurship Education; Entrepreneurship Research

Transferability as a key to impactful entrepreneurship education outcomes: a new quest - Winkler, Christoph; Jenert, Tobias; Fust, Alexander (Annals of Entrepreneurship Education and Pedagogy - 2025)
Keywords: Methodology; Entrepreneurship Education; Entrepreneurship Research

Innovation und Transfer in der kommunalen Bildungsarbeit. Erfahrungen aus zehn Jahren wissenschaftlicher Begleitung der Transferinitiative Kommunales Bildungsmanagement - Euler, Dieter; Sloane, Peter F. E.; Jenert, Tobias; Daniel-Söltenfuß, Desiree; Hagemeier, Daniel; Ludolph, Fabian; Fuhrmann, Joelle

The Multifaceted Nature of Self-Regulation in Entrepreneurship: A Latent Class Analysis - Jenert, Tobias; Büker, Ronja (21th Biennial EARLI Conference)

Innovieren, Transferieren, Gestalten: Eine Wissenschaft, die sich verständigt - Jenert, Tobias (bwp@profil)

Sustainable educational innovation in Higher Education: Upscaling, transfer, and student involvement - Jenert, Tobias

An Empirical Study of Large Language Models for Type and Call Graph Analysis in Python and JavaScript - Shivarpatna Venkatesh, Ashwin Prasad; Sunil, Rose; Sabu, Samkutty; Mir, Amir M.; Reis, Sofia; Bodden, Eric (Empirical Software Engineering)
Large Language Models (LLMs) are increasingly being explored for their potential in software engineering, particularly in static analysis tasks. In this study, we investigate the potential of current LLMs to enhance call-graph analysis and type inference for Python and JavaScript programs. We empirically evaluated 24 LLMs, including OpenAI's GPT series and open-source models like LLaMA and Mistral, using existing and newly developed benchmarks. Specifically, we enhanced TypeEvalPy, a micro-benchmarking framework for type inference in Python, with auto-generation capabilities, expanding its scope from 860 to 77,268 type annotations for Python. Additionally, we introduced SWARM-CG and SWARM-JS, comprehensive benchmarking suites for evaluating call-graph construction tools across multiple programming languages. Our findings reveal a contrasting performance of LLMs in static analysis tasks. For call-graph generation, traditional static analysis tools such as PyCG for Python and Jelly for JavaScript consistently outperform LLMs. While advanced models like mistral-large-it-2407-123b and gpt-4o show promise, they still struggle with completeness and soundness in call-graph analysis across both languages. In contrast, LLMs demonstrate a clear advantage in type inference for Python, surpassing traditional tools like HeaderGen and hybrid approaches such as HiTyper. These results suggest that, while LLMs hold promise in type inference, their limitations in call-graph analysis highlight the need for further research. Our study provides a foundation for integrating LLMs into static analysis workflows, offering insights into their strengths and current limitations.